Pre-treatment quality of life and survival in lung cancer: A bibliometric analysis - Avizova, Zeinep; Iztleuov, Yerbolat; Utepov, Parkhat; Myssayev , Ayan (Acta Biomedica Atenei Parmensis, 2025)
Background: Lung cancer, the leading cause of cancer mortality globally, severely impacts survival and quality of life. Pretreatment quality of life is a recognized prognostic factor for survival, yet a comprehensive overview of research trends in this area is lacking. This study aims to perform a bibliometric analysis of literature on pretreatment quality of life and survival in lung cancer from 2015 to 2025, mapping global patterns, key contributors, and thematic shifts to inform future oncology research. Methods: Data were sourced from the Web of Science Core Collection using queries targeting lung cancer, quality of life assessment tools (for example, the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–Core 30), pretreatment, and survival. English-language original articles from 2015–2025 were included, excluding reviews and non-articles. Following screening according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, 235 articles were analyzed using RStudio’s bibliometrix package for publication trends, citations, collaborations, and keyword frequency. Results: Analysis covered 235 studies from 110 sources, with 2497 authors and an average of 22.95 citations per document. Publications grew 4.91% annually, peaking in 2022 (>40 articles), with citations highest in 2016 (>7 per article). Leading journals included Lung Cancer (21 articles) and Journal of Clinical Oncology (623 citations). The United States (455 articles) and China (359) led production, with strong global collaborations. Top keywords were “quality of life” (68 occurrences), “chemotherapy” (66), and “survival” (61), reflecting a shift toward immunotherapy and patient outcomes. Conclusion: This study maps the evolving landscape of pretreatment quality of life and survival in lung cancer, highlighting key journals, collaborations, and emerging themes to guide future patient-centered research.